2016
DOI: 10.1039/c6py01664b
|View full text |Cite
|
Sign up to set email alerts
|

Dual-responsive nanoparticles based on oxidized pullulan and a disulfide-containing poly(β-amino) ester for efficient delivery of genes and chemotherapeutic agents targeting hepatoma

Abstract: A dual-responsive nanoparticle system was designed for the efficient delivery of genes and chemotherapeutic agents through polymer degradation responding orderly to the tumor intracellular pH and redox state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…HPPDC nanoparticles consisted of hydrophilic HA shells and hydrophobic PPDC nanocores co-loaded with a chemotherapeutic drug DOX and a COX-2 selective inhibitor CXB. Our previous investigations have shown that ssPBAE has significant amphiphilic property and can self-assemble to form nanoparticles for efficiently loading genes and/or anticancer drugs [28, 29]. Firstly, ssPBAE was synthesized and chemically characterized by 1 H NMR spectrum (Additional file 1: Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HPPDC nanoparticles consisted of hydrophilic HA shells and hydrophobic PPDC nanocores co-loaded with a chemotherapeutic drug DOX and a COX-2 selective inhibitor CXB. Our previous investigations have shown that ssPBAE has significant amphiphilic property and can self-assemble to form nanoparticles for efficiently loading genes and/or anticancer drugs [28, 29]. Firstly, ssPBAE was synthesized and chemically characterized by 1 H NMR spectrum (Additional file 1: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ssPBAE was synthesized by ourselves according to the previous report [28, 29] and the polymerization degree detected by the 1 H NMR method was about 12. HA with a molecular mass of 33 kDa was purchased from Bloomage Freda Biopharm (Jinan, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the salicylamide-modified PEI was a reliable carrier for mRNA delivery in HeLa and U87 cells [104]. As an alternative to PEI, poly (β-amino esters) (PBAEs) exhibit several advantages, such as easy synthesis, relatively low cytotoxicity, and good degradability, and have been demonstrated as an effective delivery system for nucleic acids [105, 106]. However, serum instability may be one of the drawbacks of PBAEs for systemic administration.…”
Section: Nanotechnology Platforms For Mrna Deliverymentioning
confidence: 99%
“…These findings further confirmed the specific affinity of Au@Pul-2 for hepatoma cells. In addition, the internalization of Au@Pul-2 was believed to undergo receptormediated endocytosis through binding with overexpressed ASGPR 48 .…”
Section: Cellular Internalization Of the Au@psa Nanocompositesmentioning
confidence: 99%